Mapping of Mangrove Distribution and Density in Eastern Coastal of Biak Island, Papua Using Landsat 8 Satellite Imaginary - Vivia Tablaseray; M Rizky Ardhy Pairin; Nadia Fakdawer; Baigo Hamuna (JURNAL PERIKANAN DAN KELAUTAN, 2018)
As the one of coastal resource, mangrove has socio-economic, and physical functions. Mangrove distribution and density can be identified by using remote sensing technology. Satellite images of Landsat are the most widely used for mangrove mapping. This research was conducted to determine of the mangrove distribution and density in eastern coastal of Biak Island, Papua using Landsat 8 OLI satellite imaginary, acquisition date at June 30, 2015. This research was conducted from June to August 2017, covering field data acquisition and satellite image processing. The step of mangrove identification was done by using a composite 564 RGB band, then the separation of mangrove, non-mangrove and waters objects using supervised classification method. The next step is to analyze the density of mangroves by using the formula of Normalized Difference Vegetation Index (NDVI). The result of research showed that mangrove area in eastern coastal of Biak Island was about 144.81 hectares, where the rare density 89.64 hectares, medium density 26.19 hectares and dense density 28.98 hectares. The low area of mangrove were generally caused by anthropogenic factors such as logging, changes over the function of mangroves and effect of tsunami 1996.